The potential application of electrophysiological indicators in TMS treatment for MOH - Xiao, Danqing; Han, Haochi; Guo, Huailian; Li, Zhuotong; He, Yang; Ma, Jingqi; Jiang, Hong (Frontiers in Pain Research, 2025)
Medication Overuse Headache (MOH) can lead to central sensitization (CS), habituation deficits (HD), shortened cortical silent period duration (CSPD), and increased pre-activation levels (PAL), all of which are quantifiable electrophysiological objective indicators related to MOH. Transcranial magnetic stimulation (TMS) is a treatment method for MOH and is primarily divided into three types: single-pulse TMS (sTMS), repetitive TMS (rTMS), and quadruple-pulse TMS (qTMS). Among these, sTMS is convenient for patients of self-administration, qTMS significantly improves the effectiveness of TMS treatment, and rTMS is suitable for widespread use in developing countries. Numerous studies have reported clinical symptom improvements in MOH patients treated with TMS, with statistically significant results. However, only a few studies have observed electrophysiological changes in MOH patients before and after treatment. Whether quantifiable objective indicators can be reversed requires further investigation.